PENGARUH LEVERAGE DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDENSEBAGAI VARIABEL INTERVENING (STUDI PADA PERUSAAN SUB SEKTOR PERDAGANGAN BESAR BARANG PRODUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2020) - Satrio Eko Wibowo; Zaenudin . (Jurnal Ilmiah Penelitian Mahasiswa, 2023)
The company's overall aim is to start a business, this means making a profit by maximizing resources and how companies can manage their capital, assets and capital. If a company can maximize its resources, it is likely that the company will earn big profits, so it can affect the company's value in the eyes of investors (Gultom, 2013). The research method used is quantitative. With its type that is associative. The results of this study Leverage does not affect firm value. Leverage does not affect the value of the company so that investors only see the returns they receive regardless of the debt; Liquidity has a positive effect on company value, meaning that high liquidity can fulfill the company's short-term obligations so that the company's operations are not disrupted; The greater the interest of investors in saving capital, the higher the stock price which will affect the value of the company; Leverage has a positive effect on the dividend policy of companies with high operating or financial debt paying low dividends; Liquidity has a positive effect on dividend policy; Dividend policy does not mediate the leverage variable in firm value; Dividend policy can mediate the variables of liquidity and firm value. Keywords: leverage, liquidity, companu value